Implementasi Analytical Hierarchy Process-Topsis Dalam Penentuan Marketplace Terbaik Di Indonesia - Rice Novita; Akhas Rahmadeyan; Vina Vamilina (Building of Informatics, Technology and Science (BITS), 2022)
The marketplace industry in Indonesia is starting to grow rapidly over time. Behind the convenience, some users still feel dissatisfied when making transactions. Problems that are often encountered are product incompatibility, delivery problems, types of payment methods, unsatisfactory service, to difficult return policies. In addition, many considerations such as prices, discounts, and promos make users confused about choosing the right marketplace to make transactions. This study applies the AHP-TOPSIS method as decision support to determine the best marketplace in Indonesia with the criteria used, namely discounts & promos, services, features, product quality, payment methods, and availability of goods. While the alternatives used are Tokopedia, Shopee, Blibli, Lazada, and Bukalapak. The results of the implementation with the AHP-TOPSIS method resulted in Shopee being the best marketplace recommendation with a preference value of 0.9897, followed by Tokopedia with a value of 0.7289, Lazada with a value of 0.4145, Bukalapak with a value of 0.0641 and Blibli with a value of 0.0059. The results of this study are expected to be useful for the community in making decisions on choosing the marketplace that best suits their needs and circumstances for conducting transactions